Cell surface properties of HLA antigens on Epstein-Barr virus-transformed cell lines. - Smith, L M (1982)
A number of monoclonal antibodies have been used to investigate the distributions and rates of lateral motion of the HLA-A,B, and-DR antigens on several Epstein--Barr virus-transformed B-cell lines. The lateral diffusion coefficients (D) of fluorescein conjugates of the monoclonal antibodies bound to the cell surface were determined by fluorescence recovery after pattern photobleaching. Ds of HLA-A and-B were found to be comparable and of the order of 10(-9) to 10(-10) cm2/sec for each of the seven monoclonal antibodies and four cell lines examined. The HLA antigens appear to be monomeric on the cell surface based on experiments using mixtures of arsanilic acid-conjugated and fluorescein-conjugated antibodies. Four monoclonal antibodies against DR antigens were examined. Two of these, Genox 3.53 and L243, labeled the cell surface uniformly and gave Ds comparable to those obtained for the HLA-A and -B antigens. The other two, DA2 and 2.06, rapidly patched on the cell surface and were immobile. The DA2, L243, and Genox 3.53 antibodies bound outside of the caps formed with the arsanilic acid-conjugated 2.06 antibody and a second-step rhodamine-conjugated rabbit anti-arsanilate antibody. This is consistent with recent biochemical evidence that there are multiple distinct antigens coded for by the HLA-DR region.